Maca modulates fat and liver energy metabolism markers insulin, IRS1, leptin, and SIRT1 in rats fed normal and high-fat diets - Gencoglu, Hasan (Taylor & Francis Ltd, 2023)
Maca root extract on insulin, insulin receptor substrate-1 (IRS1), leptin, and NAD-dependent deacetylase sirtuin-1 (SIRT1), as well as body weight changes evaluated in this study for a 60 days model of normal and high-fat diet (HFD) fed rats. 28 male rats allocated to four groups: (i) Control, (ii) Maca (40 mg/kg/day), (iii) HFD, and (iv) HFD + Maca. After the 60 days of study, fat tissue and liver insulin levels decreased in the HFD and HFD + Maca groups in comparison to Control and Maca groups (p < .001). Maca group showed a significant IRS1 increase in the fat tissue (p < .0001). Leptin levels were the highest in the Maca group and the lowest in the HFD group in the fat tissue (p < .01). SIRT1 levels were found the highest in the Maca groups (p < .01). These results show the protective and regulatory effectiveness of Maca when fed with a normal or HFD diet.
Keywords: Energy metabolism; inflammation; Maca Root; obesity; sirtfood